2012
DOI: 10.1583/jevt-12-4042r.1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Balloon for Treatment of In-Stent Restenosis After Carotid Artery Stenting: Preliminary Report

Abstract: The use of DEBs to treat ISR after CAS shows promising acute and midterm results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 28 publications
(30 reference statements)
1
47
0
Order By: Relevance
“…Subsequently, this information must be translated to the clinical arena by RCTs to confirm DEB efficacy in patients affected by atherosclerotic disease in both coronary and peripheral districts. The pioneering application of DEB technology to carotid ISR by Liistro 11 and Montorsi 12 and their colleagues deserves our congratulations. However, only when RCTs are performed in this setting will we know if the DEB technology can deliver the goods in the battle against restenosis.…”
Section: Endovasc Ther Commentarymentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, this information must be translated to the clinical arena by RCTs to confirm DEB efficacy in patients affected by atherosclerotic disease in both coronary and peripheral districts. The pioneering application of DEB technology to carotid ISR by Liistro 11 and Montorsi 12 and their colleagues deserves our congratulations. However, only when RCTs are performed in this setting will we know if the DEB technology can deliver the goods in the battle against restenosis.…”
Section: Endovasc Ther Commentarymentioning
confidence: 96%
“…The optimal immediate angiographic results were durable over a follow-up that extended from 6 to 24 months. In a subsequent article, Montorsi and coauthors 12 reported 10 cases of ISR at a mean 20.9619.4 months after carotid artery stenting (CAS) among 830 consecutive CAS procedures. Seven of the 10 patients were treated with DEBs (1 common and 6 internal carotid arteries).…”
mentioning
confidence: 99%
“…The first is the "wire reshaping" technique that keeps the wire below the bifurcation, limiting the risk of inadvertently crossing the lesion, maintaining good support for advancing the whole system. 23 The second is the use of the Mo.MA mono balloon without the Y-connector, allowing the mandrel to stick out 8.5 cm of the catheter tip ( Figure 6B). Alternatively, the mandrel can be exchanged for a 4-F, 125-cm-long multipurpose catheter that provides a longer transition zone (up to 20 cm; Figure 6C).…”
Section: Maccementioning
confidence: 99%
“…No new ISR developed at mean 13.7 13 and 14 14 months. Since our first report, 13 2 additional patients have been treated, and the average follow-up has been extended to 28639 months. Interestingly, the individual PSV values after DCB remained flat (~1 m/s) in all cases, confirming the long-term safety and efficacy of this device (Fig.…”
mentioning
confidence: 99%
“…3 Secondly, it has been shown that not all the DCBs have a similar antiproliferative effect due to differences in drug delivery technology, excipient, and dose of paclitaxel. 16,17 Favorable initial results have been reported with the IN.PACT DCB technology for treatment of both coronary and peripheral artery ISR, 13,14,[18][19][20][21] whereas the DIOR II DCB technology has been tested in a few studies and needs further confirmation. [21][22][23][24] Finally, lesion preparation and DCB sizing are crucial points of this therapeutic strategy.…”
mentioning
confidence: 99%